2023
DOI: 10.1111/nph.18757
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐responsive SbWRKY50 suppresses leaf senescence by inhibition of chlorophyll degradation in sorghum

Abstract: Summary The onset of leaf de‐greening and senescence is governed by a complex regulatory network including environmental cues and internal factors such as transcription factors (TFs) and phytohormones, in which ethylene (ET) is one key inducer. However, the detailed mechanism of ET signalling for senescence regulation is still largely unknown. Here, we found that the WRKY TF SbWRKY50 from Sorghum bicolor L., a direct target of the key component ETHYLENE INSENSITIVE 3 in ET signalling, functioned for leaf sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…TaWRKY42-B promotes leaf senescence by regulating TaLOX3 gene expression, thereby enhancing JA biosynthesis [78]. In sorghum, overexpression of SbWRKY50 delayed age-dependent and dark-induced senescence [79]. SbWRKY50 is a direct target of the key component ETHYLENE INSENSITIVE 3 in ethylene signaling but functions as a negative regulator of leaf senescence by suppressing chlorophyll catabolic pathway via directly repressing SbNYC1 (NON-YELLOW COLORING 1) [79], suggesting that SbWRKY50 may act as a braking device for the signaling pathway of ethylene-induced leaf senescence.…”
Section: Wrky Tfs-regulated Leaf Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…TaWRKY42-B promotes leaf senescence by regulating TaLOX3 gene expression, thereby enhancing JA biosynthesis [78]. In sorghum, overexpression of SbWRKY50 delayed age-dependent and dark-induced senescence [79]. SbWRKY50 is a direct target of the key component ETHYLENE INSENSITIVE 3 in ethylene signaling but functions as a negative regulator of leaf senescence by suppressing chlorophyll catabolic pathway via directly repressing SbNYC1 (NON-YELLOW COLORING 1) [79], suggesting that SbWRKY50 may act as a braking device for the signaling pathway of ethylene-induced leaf senescence.…”
Section: Wrky Tfs-regulated Leaf Senescencementioning
confidence: 99%
“…In sorghum, overexpression of SbWRKY50 delayed age-dependent and dark-induced senescence [79]. SbWRKY50 is a direct target of the key component ETHYLENE INSENSITIVE 3 in ethylene signaling but functions as a negative regulator of leaf senescence by suppressing chlorophyll catabolic pathway via directly repressing SbNYC1 (NON-YELLOW COLORING 1) [79], suggesting that SbWRKY50 may act as a braking device for the signaling pathway of ethylene-induced leaf senescence. OsWRKY5 promotes leaf senescence in rice by regulating the expression of Sen-NAC TFs, including OsNAP and OsNAC2 [80].…”
Section: Wrky Tfs-regulated Leaf Senescencementioning
confidence: 99%
“…Previous research has demonstrated that ROS play a role in controlling plant senescence and that high levels of ROS during leaf senescence cause oxidative damage to lipids, proteins, and DNA (Chen et al, 2023). In this study, the quantification and histochemical analysis of O 2 ·− and H 2 O 2 revealed a clear ROS accumulation in dark‐induced senescent cucumber leaves, but this accumulation was lower in leaves with increased TOR activity/expression (Figure 2‐3).…”
Section: Discussionmentioning
confidence: 99%
“…As leaves ages, the photosynthetic activity of chloroplasts decreases, leading to inadequate energy and nutrient supply (Kobayashi, 2016; Li & Kim, 2022). The chlorophyll in chloroplasts gradually breaks down, causing leaves to turn yellow (Chen et al, 2023). Additionally, chloroplasts release nitrogen that can be recycled and utilized for new growth (Domínguez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it promotes ET synthesis by directly stimulating ACS2, thereby accelerating leaf senescence in Arabidopsis. However, a recent study found that transcription factor SbWRKY50 in Sorghum bicolor hinders chlorophyll degradation by binding to chlorophyll catabolic gene promoters, notably repressing SbNYC1 (NON-YELLOW COL-ORING 1), thus suppressing leaf senescence [138]. Petal senescence is another phase in the flower developmental continuum accompanied by tissue differentiation, petal maturation, and finally, the growth and development of seeds coordinated by plant hormones [22].…”
Section: Senescencementioning
confidence: 99%